(untitled) (Research, Society and Development, 2021)
This article presents an experience report about inclusive education, with a clipping for the specialized educational care performed in the Multifunctional Resources Room (MRR), pointing out how planning based on Bloom taxonomy can contribute to the significant learning of the student, in particular, the target audience of special education attended in the MRR within the regular schools. In this sense, it is intended to dialogue about teaching strategies and seek the light of theories means for an autonomous learning to be effective, based on the educational objectives proposed for each level of education. This analysis was performed with a student with moderate intellectual disability, speech articulation difficulties and who does not present mental organization domains expected for age. The student has multiprofessional follow-up in the health area, which is carried out in partnership with the school professionals. It is worth mentioning that this collaborative work among health and education professionals has brought numerous benefits to student development.